2013
DOI: 10.1002/2013gl057973
|View full text |Cite
|
Sign up to set email alerts
|

Measuring water accumulation rates using GRACE data in areas experiencing glacial isostatic adjustment: The Nelson River basin

Abstract: International audienceGravity Recovery and Climate Experiment (GRACE) satellite-derived total water storage can be obscured by glacial isostatic adjustment. In order to solve this problem for the Nelson River drainage basin in Canada, a gravity rate map from 110 months (June 2002 to October 2011) of GRACE gravity data was corrected for glacial isostatic adjustment using an independent gravity rate map derived from updated GPS vertical velocities. The GPS-based map was converted to equivalent gravity rate using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 24 publications
0
48
0
Order By: Relevance
“…The changes in terrestrial water storage ( TWS) derived from the Gravity Recovery And Climate Experiment (GRACE) data products have been used in the last decade to study global water resources, including groundwater depletion in India and the Middle East (Rodell et al, 2009;Voss et al, 2013), water storage accumulation in Canada (Lambert et al, 2013), and flood-influenced water storage fluctuation in Cambodia (Tangdamrongsub et al, 2016). The gravity data obtained from GRACE satellites are commonly processed and released in three different product levels (L) that increase in the amount of processing, L1B -satellite tracking data (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The changes in terrestrial water storage ( TWS) derived from the Gravity Recovery And Climate Experiment (GRACE) data products have been used in the last decade to study global water resources, including groundwater depletion in India and the Middle East (Rodell et al, 2009;Voss et al, 2013), water storage accumulation in Canada (Lambert et al, 2013), and flood-influenced water storage fluctuation in Cambodia (Tangdamrongsub et al, 2016). The gravity data obtained from GRACE satellites are commonly processed and released in three different product levels (L) that increase in the amount of processing, L1B -satellite tracking data (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The utility of the technique was extended to a 300 m deep well by Sophocleous et al [2006], and Bardsley and Campbell [2007] showed that using piezometric measurements in two formations improved accuracy compared to measurements from a single piezometer. Lambert et al [2013] showed that the total moisture changes recorded by observation wells in deep confined aquifers correlate well with total gravity changes determined from the GRACE gravity changes.…”
Section: Introductionmentioning
confidence: 55%
“…In Canada, non-water mass (mainly the Earth's crust and mantle) redistribution is largely caused by the glacial isostatic adjustment (GIA) around the Hudson Bay, which is removed using the GPS-derived GIA estimation as discussed in Lambert et al (2013). The TWS variations after the GIA correction have been extracted from the GRACE models by the two-step method (Huang et al 2012), which has been modified by adapting its parameters to RL05 models.…”
Section: Methodsmentioning
confidence: 99%
“…The monthly degree-two term C 20 time series is better determined by the satellite laser ranging (Cheng et al 2013), and is thus used to replace the corresponding C 20 of each GRACE model. In addition, a gravity rate map derived from the GPS vertical velocity map using the ratio between the gravity change rates by absolute gravity measurements and the GPS vertical velocities at the same locations was used to remove the mass redistribution effect due to the glacial isostatic adjustment (Lambert et al 2013).…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation